The First Transition Metal Complexes of 15-Membered Triolefinic Macrocycles: (E,E,E)-1,6,11-Tris(arenesulfonyl)-1,6,11-triazacyclopentadeca-3,8,13-triene Complexes of Palladium(0), Platinum(0), and Silver(I) - Cerezo, Silvia; Cortès, Jordi; Lago, Elena; Molins, Elies; Moreno-Mañas, Marcial; Parella, Teodor; Pleixats, Roser; Torrejón, Javier; Vallribera, Adelina (European journal of inorganic chemistry, 2001)
(E,E,E)‐1,6,11‐Tris(arenesulfonyl)‐1,6,11‐triazacyclopentadeca‐3,8,13‐trienes (1) form very stable complexes with Pd0 and Pt0, and moderately stable complexes with AgI. The three olefins in the macrocycle are responsible for the complexation. The X‐ray structures of two complexes of Pd0 and Pt0 are presented; both complexes are planar trigonal.